Effect of concomitant use of yokukansan on steady‐state blood concentrations of donepezil and risperidone in real‐world clinical practice - Junji Saruwatari; Tetsuya Kaneko; Tsukasa Murata; Haruka Narise; Sawa Kugimoto; Eri Nishimura; Natsuki Tetsuka; Misaki Ando; Momo Oi; Masako Ota; Nayumi Hamada; Keiichiro Kaneda; et al. (Wiley, 2024)
Abstract Aim Yokukansan is one of the most frequently used herbal medicines that can improve the behavioral and psychological symptoms of dementia. In this exploratory study, we investigated whether yokukansan affects the steady‐state blood concentrations of donepezil, risperidone, and the major metabolites of both drugs in a real‐world clinical setting. Methods A non‐randomized, open‐label, single‐arm study examining drug-drug interactions was conducted. Fifteen dementia patients taking donepezil for at least 4 weeks and eight schizophrenia patients taking risperidone for at least 2 weeks were orally administered 2.5 g of yokukansan three times a day before or between meals, and blood samples were collected before and 8 weeks after starting co‐treatment with yokukansan. Plasma concentrations of donepezil, risperidone, and each metabolite were measured using high‐performance liquid chromatography-tandem mass spectrometry and compared before and after the 8‐week administration of yokukansan. Results The plasma concentrations of donepezil and its metabolites (6‐O‐desmethyl‐donepezil, 5‐O‐desmethyl‐donepezil, and donepezil‐N‐oxide), risperidone, and its metabolite paliperidone did not differ before and after the 8‐week treatment with yokukansan. Conclusions The findings of this study show that the concomitant use of yokukansan may have little clinical impact on the steady‐state blood levels of donepezil and risperidone in patients with dementia or schizophrenia.